Brief communication: Carrier rate, antimicrobial resistance and molecular typing of Staphylococcus aureus and Staphylococcus pseudintermedius in healthy dogs from Morogoro, Tanzania - Katakweba, A.A.S.; Iversen, C.M.; Tsaxra, J.B.; Muhairwa, A.P.; Moodley, Arshnee; Olsen, J.E. (Wiley, 2024)
Background: Staphylococcus pseudintermedius and S. aureus are important pathogens in dogs. This study established carrier rates, strain diversity and antimicrobial resistance of these bacteria among healthy dogs in Tanzania.